Emergency Management System in Lithuania: Functions and Complications to Implement them - Pitrenaite, B. (Наука та наукознавство, 2007)
The paper contains an analysis into the government’s actions in emergency situations, by describing of the structure of the emergency system, listing of the institutions engaged in emergency control, and analyzing their functions. У статті аналізуються дії держави в умовах екстремальних ситуацій, описано структуру системи управління екстремальними ситуаціями (УЕС), визначено інституції, що беруть участь в УЕС, аналізуються їх функції. В статье анализируются действия государства в условиях экстремальных ситуаций, описывается структура системы управления экстремальными ситуациями (УЭС), определены институции, участвующие в УЭС, анализируются их функции.